Do Environmental Regulations Attract Foreign Direct Investment Inflows in OIC Countries? - Santika, Ana; Azzaki, Muhammad Adnan; Arifin, Ah. Ali (Department of Development Economics, Universitas Sriwijaya, 2025)
This study investigates the controversial impact of environmental regulations and foreign direct investment (FDI) inflows, specifically in 32 Organization of Islamic Cooperation (OIC) countries from 2005 to 2020. Challenging the widely debated